Determination of the Feed Value of Leaves of Various Mulberry of Syrdarya Region - Rajabov, N. O.; Raxmonberdiyev, V. K. (American Journal of Botany and Bioengineering, 2024)
The article analyzes the results of studies on the creation of fodder plantations from the mulberry variety Jararik-10. The results obtained allow us to assert that the Jararik -10 variety is by all indicators the most productive, salt-resistant and adapted to the conditions of saline soils in the Syrdarya region. The variety exceeds the control in terms of leaf yield during double operation by 12.14%, cocoons by 13.01% and raw silk yield by 24%. Among the studied varieties, only this one can be recommended for widespread introduction of sericulture in this region.